Antroponimika – nomshunoslikning shaxs ismlarini o’rganuvchi bo’limi - Ibrohimova, D (SCIENCE and SOCIETY, 2019)
In the article we made an attempt to investigate the etymology of English proper names and characteristic features of their verbaliza- tion in the language national picture of the world. Such kind of research is important also from theoretical and practical points of view. Hypothesis in Linguistics and Etymology helped to study proper names is different discourses and all these works enriched our research work and confirmed our conclusions.
Keywords: word; life of nation; history; development; customs; traditions; personal names; anthroponimics; motivation; etymology; structure